2010
DOI: 10.1097/hjh.0b013e32833b4a6f
|View full text |Cite
|
Sign up to set email alerts
|

The association of depression with adherence to antihypertensive medications: a systematic review

Abstract: Objective-To examine the strength and consistency of the evidence on the relationship between depression and adherence to antihypertensive medications.Methods-The MEDLINE, CINAHL, PsycINFO, Embase, SCOPUS, and ISI databases were searched from inception until December 11, 2009 for published studies of original research that assessed adherence to antihypertensive medications and used a standardized interview, validated questionnaire or International Classification of Diseases Ninth Revision (ICD-9) code to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 45 publications
5
36
0
8
Order By: Relevance
“…The strong association between depression and difficulty with adherence was expected and was consistent with the findings of earlier research conducted among patients with MS [10, 13]. It also was consistent with research showing the negative effect of comorbid depression on adherence to therapy for other diseases, including hypertension [38], diabetes [10, 11], and heart disease [39, 40]. While previous research among patients with MS has shown comorbid depression to be associated with adherence difficulties [10, 13], our research expands the literature by quantifying the adherence gap between those MS patients with comorbid depression compared to those without depression.…”
Section: Resultssupporting
confidence: 89%
“…The strong association between depression and difficulty with adherence was expected and was consistent with the findings of earlier research conducted among patients with MS [10, 13]. It also was consistent with research showing the negative effect of comorbid depression on adherence to therapy for other diseases, including hypertension [38], diabetes [10, 11], and heart disease [39, 40]. While previous research among patients with MS has shown comorbid depression to be associated with adherence difficulties [10, 13], our research expands the literature by quantifying the adherence gap between those MS patients with comorbid depression compared to those without depression.…”
Section: Resultssupporting
confidence: 89%
“…Additionally, a number of sociodemographic correlates of poor adherence to medical therapy have been identified in the general population and include being female, non-white, younger, less education, lower income, living alone, non-married, and having an unstable living environment (Rolnick et al, 2013; Wheeler et al, 2014). There is also extensive evidence that psychological factors, such as depression, are associated with a decline in adherence to medications for various chronic medical conditions (Eze-Nliam, Thombs, Lima, Smith, & Ziegelstein, 2010; King et al, 2012; Osborn & Egede, 2012; Wheeler et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…4,5 Because HTN self-management NA is modifiable, identifying non-adherent patients is essential. Despite recognizing the influence of demographic, psychosocial, socioeconomic, and health belief-related factors on HTN self-management NA, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] physicians have difficulty identifying non-adherent patients. Existing HTN NA prediction instruments are often complex and none are widely accepted.…”
Section: Introductionmentioning
confidence: 99%